DAUR HID UP KUMBANG "LADYBIRD" Epilachna Vigintioctopunctata (Fabricius) (COLEOPTERA, COCCINELLIDAE, EPILACHNINAE) PADA TANAMAN LEUNCAK (Solanum nigrum Linn.) (SOLANACEAE) - Kahono, Sih (ZOO INDONESIA, 1993)
Abstrak